Geo-engineered dredged marine sediments via induced consolidation and heat treatment for reclamation works - Chong, Wen-Jing; Chan, Chee-Ming; Tuan Ismail, Tuan Noor Hasanah (Penerbit UTHM, 2020)
Typically, dredged marine sediments (DMS) are soft, relatively poor in engineering properties and contaminated from upstream sources. DMS are therefore routinely discarded inland or offshore, inadvertently raising contamination risks throughout the process. However, with pre-treatment to both eliminate the contaminants and to enhance the engineering properties, DMS can be reused as backfills in reclamation works. The present study examines the combination of preloading and heating to address the aformentioned problems. 1D compressibility tests with the standard oedometer were executed at incremental loads of 5, 10, 20, 40 and 80 kPa to examine the material’s consolidation behaviour. The consolidated sample from each loading was then subjected to staged heat treatment at 105, 350, 550 and 650 °C to decontaminate the DMS. The contamination level was indirectly assessed via electrical conductivity (EC) and pH measurements at predetermined time intervals of heating for 24 hours. The oedometer tests showed significant improvement in terms of settlement control under preloading of the DMS, where excess pore water was forcefully discharged to induce consolidation and stiffening of the soil. As for the heat treatment, both EC and pH readings indicated the highest chemical activity in the temperature window of 300-400oC, suggesting an optimal decontamination rate for all preloading cases within the temperature range. In summary, combined preloading and heat treatment of DMS could reduce post-construction settlement of the DMS in reclamation works as well as the contamination risks, where field application would require an incorporated removal system for the dissolved contaminants.